HAM di Indonesia: Menuju 'Democratic Governances' - Kurniarpan Kunto Yuliarso; Nunung Prajarto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Democratic governance requires the existence of good governance, human rights and democracy. Obtaining the standards of democratic governance is needed by Indonesia to be internationally accepted. Nonetheless, Indonesia's record on human rights leads to the understanding that this country has to pay highly attention on human rights, Five elements can be contested to evaluate the position of Indonesia in achieving the democratic governance.